2014
DOI: 10.1177/2042018814529062
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic effects of vildagliptin in patients with type 2 diabetes before, during and after the period of fasting in Ramadan

Abstract: Objective: To study the incidence of hypoglycemia, glycemic control and body weight changes in patients with type 2 diabetes treated with vildagliptin and metformin versus another group treated with sulphonylureas and metformin during and after the period of fasting in Ramadan. Patients and methods: This is a randomized open-label clinical trial that recruited 69 patients previously treated with a combination therapy of metformin and sulphonylurea. Patients in the control group were maintained on their usual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 14 publications
(26 reference statements)
1
37
0
Order By: Relevance
“…Four RCTs have examined the effects of switching from SU therapy to either vildagliptin or sitagliptin prior to Ramadan compared with continuing on SUs [31,33,36,42]. The largest of these studies compared the incidence of self-reported hypoglycaemic events in 1066 patients with T2DM treated with sitagliptin or SUs during Ramadan.…”
Section: Dipeptidyl Peptidase-4 (Dpp-4) Inhibitorsmentioning
confidence: 99%
“…Four RCTs have examined the effects of switching from SU therapy to either vildagliptin or sitagliptin prior to Ramadan compared with continuing on SUs [31,33,36,42]. The largest of these studies compared the incidence of self-reported hypoglycaemic events in 1066 patients with T2DM treated with sitagliptin or SUs during Ramadan.…”
Section: Dipeptidyl Peptidase-4 (Dpp-4) Inhibitorsmentioning
confidence: 99%
“…Primary outcome for all the nine studies is the number of hypoglycemic events. Six studies compared both the changes in HbA1C and weight pre and post Ramadan in both groups of patients [13,15,[17][18][19]21]. Three studies assessed the treatment compliance during Ramadan [15,17,18].…”
Section: Data Synthesismentioning
confidence: 98%
“…All of the included patients were type 2 diabetes mellitus 18 years or older. Seven studies used Vildagliptin as the DPP4 inhibitor of choice [13,15,[17][18][19][20][21] whereas the other two studies used Sitagliptin [14,16]. All of the studies had a control group using sulphonylurea (glipizide, glibenclamide, glimepiride, gliclazide slow release or gliclazide standard formulation) or the other insulin secretagogue -meglitinides.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…antidiabetic choice for Ramadan with practically no hypoglycemia risk. 6 For patients with DM2 on insulin or patients with DM1, a basal-bolus regimen is advised, 2,5 taking, however, into account the paucity of relevant data. 5 A 20% dosing reduction in long-acting insulin analogues, given with Iftar, has been proposed to reduce the risk of hypoglycemia.…”
Section: Letter To the Editormentioning
confidence: 99%